2017
DOI: 10.1002/ardp.201700028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biological Evaluation of Some Novel Quinoxaline Derivatives as Antiviral Agents

Abstract: Ethyl (6,7-dimethyl-2-oxo-3,4-dihydroquinoxalin-3-yl)acetate and ethyl (6-methyl-2-oxo-3,4-dihydroquinoxalin-3-yl)acetate (1a,b), 3-methylquinoxalin-2(1H)-one (4) and 1,4-dihydroquinoxaline-2,3-dione (11) were the starting precursors for nine novel quinoxaline compounds, 3a, 6, 10, 13, 15, 16, 17, 18, and 20, via adopting different nucleophilic reactions. The synthesized compounds were tested for their antiviral activity against HCV, HBV, HSV-1, and HCMV. Concomitantly, their safety profile was investigated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Several quinoxaline derivatives were evaluated for their anti-HCV potential. Even though novel quinoxaline derivatives synthetized using ethyl (6,7-dimethyl-2-oxo-3,4-dihydroquinoxalin-3-yl)acetate 4 and ethyl (6-methyl-2-oxo-3,4-dihydroquinoxalin-3-yl)acetate 5 , 3-methylquinoxalin-2(1 H )-one, and 1,4-dihydroquinoxaline-2,3-dione as precursors failed to demonstrate any activity against HCV [ 31 ], in pyrido[2,3- g ]quinoxalinone series, 5-chloro-3-(thiophen-2-yl)pyrido[2,3- g ]quinoxaline-2(1 H )-one 16 ( Figure 11 ) was able to inhibit HCV replication in a subgenomic replication assay with EC 50 = 7.5 ± 0.5 µM. However, it was also cytotoxic for GS4.1 cells (CC 50 = 21 ± 20 µM) [ 37 , 38 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several quinoxaline derivatives were evaluated for their anti-HCV potential. Even though novel quinoxaline derivatives synthetized using ethyl (6,7-dimethyl-2-oxo-3,4-dihydroquinoxalin-3-yl)acetate 4 and ethyl (6-methyl-2-oxo-3,4-dihydroquinoxalin-3-yl)acetate 5 , 3-methylquinoxalin-2(1 H )-one, and 1,4-dihydroquinoxaline-2,3-dione as precursors failed to demonstrate any activity against HCV [ 31 ], in pyrido[2,3- g ]quinoxalinone series, 5-chloro-3-(thiophen-2-yl)pyrido[2,3- g ]quinoxaline-2(1 H )-one 16 ( Figure 11 ) was able to inhibit HCV replication in a subgenomic replication assay with EC 50 = 7.5 ± 0.5 µM. However, it was also cytotoxic for GS4.1 cells (CC 50 = 21 ± 20 µM) [ 37 , 38 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of four new aldehydo-sugar-N-(3-phenylquinoxalin-2-yl)hydrazones 2a-d and their acyclic C-nucleoside analogues, 1-(4-phenyl- [1,2,4]triazolo [4,3-a]quinoxalin-1-yl)alditols 3a-d ( Figure 4) indicated that these compounds exhibited very weak antiviral activity against HSV-1 in a plaque reduction infectivity assay in comparison to aphidicolin taken as reference [30]. Recently, nine novel quinoxaline derivatives were synthetized via different nucleophilic reactions using ethyl (6,7-dimethyl-2-oxo-3,4-dihydroquinoxalin-3-yl)acetate 4 and ethyl (6-methyl-2-oxo-3,4-dihydroquinoxalin-3-yl)acetate 5, 3-methylquinoxalin-2(1H)-one, and 1,4dihydroquinoxaline-2,3-dione as precursors [31] (Table 3). When their antiviral activity against HCMV was compared to the standard drug ganciclovir (EC50 = 0.059 µM), two derivatives demonstrated higher activity, each with EC50 < 0.05 µM.…”
Section: Quinoxaline Derivatives Active Against Herpesviridaementioning
confidence: 99%
See 1 more Smart Citation
“…Nine quinoxaline derivatives were prepared and evaluated for their antiviral activity against hepatitis C virus (HCV), hepatitis B virus (HBV), HSV-1, and human cytomegalovirus HCMV by El-Zahabi [ 175 ]. The in vitro screening data indicated that the pyridinyl triazole derivative 198 ( Fig.…”
Section: Biological Activities Of 124-triazole Derivativesmentioning
confidence: 99%
“…Enaminones bearing a 3,4‐dihydroquinoxalin‐2(1 H )‐one core (QOs) are a promising class of biologically active compounds. They were found to exhibit anticancer, anti‐inflammatory, antidiabetic, analgesic, antiviral, and antimicrobial activities (Figure ). In addition, these compounds are versatile and available building blocks enabling synthesis of various quinoxaline‐based heterocyclic systems…”
Section: Introductionmentioning
confidence: 99%